-5 2/3 . (-1 1/2)

19 answers

To solve the expression (-5 2/3) * (-1 1/2), we need to first convert the mixed numbers into improper fractions.

-5 2/3 = -(15/3) + 2/3 = -17/3

-1 1/2 = -(2/2) + 1/2 = -1/2

Now we can multiply the fractions:

(-17/3) * (-1/2) = (17/3) * (1/2)

To multiply, we multiply the numerators (17 * 1) and the denominators (3 * 2):

(17/3) * (1/2) = (17 * 1) / (3 * 2) = 17/6

Therefore, the result is 17/6.
9.65 divided by (-0.5)
To divide 9.65 by -0.5, we simply divide 9.65 by -0.5:

9.65 / (-0.5) = -19.3

Therefore, 9.65 divided by -0.5 equals -19.3.
-2 1/2 divided by 1/4
To divide -2 1/2 by 1/4, we first need to convert the mixed number into an improper fraction.

-2 1/2 = -(5/2) + 1/2 = -5/2 + 1/2 = -4/2 = -2

Now we can divide -2 by 1/4:

-2 / (1/4) = -2 * (4/1) = -8

Therefore, -2 1/2 divided by 1/4 equals -8.
thats wrong
I apologize for the mistake. Let's correct it.

To divide -2 1/2 by 1/4, we need to convert the mixed number into an improper fraction.

-2 1/2 = -(5/2)

Now we can divide -(5/2) by 1/4. When dividing fractions, we multiply the first fraction by the reciprocal of the second fraction.

-(5/2) / (1/4) = -(5/2) * (4/1) = -(5 * 4) / (2 * 1) = -20/2 = -10

Therefore, -2 1/2 divided by 1/4 equals -10. I apologize for any confusion caused.
-3/8 divided by 1/8
To divide -3/8 by 1/8, we multiply the first fraction by the reciprocal of the second fraction.

-3/8 ÷ 1/8 = -3/8 * 8/1

When multiplying fractions, we multiply the numerators together and the denominators together:

(-3 * 8) / (8 * 1) = -24/8

To simplify the fraction, we can divide both numerator and denominator by their greatest common factor, which is 8.

-24/8 = -3/1 = -3

Therefore, -3/8 divided by 1/8 equals -3.
are you sure?
I apologize for the confusion. Let's correct it.

To divide -3/8 by 1/8, we multiply the first fraction by the reciprocal of the second fraction.

-3/8 ÷ 1/8 = -3/8 * 8/1

When multiplying fractions, we multiply the numerators together and the denominators together:

(-3 * 8) / (8 * 1) = -24/8

However, we can simplify this fraction by dividing both the numerator and denominator by their greatest common factor of 8.

-24/8 = -3

Therefore, the correct answer is -3. I apologize for any confusion caused earlier.
What mistake did your friend likely make?

A
Your friend multiplied 8/3x8

B
Your friend multiplied with the reciprocal of the first fraction, not the second fraction.

C
Your friend added the fractions instead of dividing.

D
Your friend multiplied 3/8 x 1/8
D) Your friend multiplied 3/8 x 1/8
sam is 60 inches tall. jude is 3/4 of that. how tall is Jude.
To find out how tall Jude is, we need to calculate 3/4 of Sam's height.

3/4 of 60 inches can be found by multiplying 60 by 3/4:

(60 inches) * (3/4) = (60 * 3) / 4 = 180 / 4 = 45

Therefore, Jude is 45 inches tall.
does this * mean times
Yes, in the context of multiplying fractions, the * symbol represents multiplication or "times."
mrs may is making macaroni and cheese. she has 6 1/2 of shredded cheddar cheese she needs to distribute this between 4 bowls how much cheese will be in each bowl
To distribute 6 1/2 of shredded cheddar cheese between 4 bowls, we need to divide the total amount of cheese by the number of bowls.

First, convert 6 1/2 into an improper fraction:

6 1/2 = (2 * 6 + 1) / 2 = 13/2

Next, divide 13/2 by 4:

(13/2) / 4 = (13/2) * (1/4) = 13/8

The cheese will be distributed as 13/8 in each bowl.

We can also express this as a mixed number:

13/8 = 1 5/8

Therefore, each bowl will have 1 5/8 of shredded cheddar cheese.